2014
DOI: 10.1016/j.exer.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational modification of mitochondrial transcription factor A in impaired mitochondria biogenesis: Implications in diabetic retinopathy and metabolic memory phenomenon

Abstract: Mitochondrial transcription factor A (TFAM) is one of the key regulators of the transcription of mtDNA. In diabetes, despite increase in gene transcripts of TFAM, its protein levels in the mitochondria are decreased and mitochondria copy numbers become subnormal. The aim of this study is to investigate the mechanism(s) responsible for decreased mitochondrial TFAM in diabetes. Using retinal endothelial cells, we have investigated the effect of overexpression of cytosolic chaperone, Hsp70, and TFAM on glucose-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…7 Santos, et al have shown that ubiquitination of TFAM in diabetes prevents its transport to the mitochondria, which disrupts mitochondrial homeostasis indicating the strong relation with diabetes and mitochondrial dysfunction. 7 Kearns-Sayre Syndrome (KSS) is a rare cause of diabetes in children. KSS has a group of diseases, known as the classic triad, which includes retinitis pigmentosa, progressive external ophthalmoplegia, and cardiac conduction problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Santos, et al have shown that ubiquitination of TFAM in diabetes prevents its transport to the mitochondria, which disrupts mitochondrial homeostasis indicating the strong relation with diabetes and mitochondrial dysfunction. 7 Kearns-Sayre Syndrome (KSS) is a rare cause of diabetes in children. KSS has a group of diseases, known as the classic triad, which includes retinitis pigmentosa, progressive external ophthalmoplegia, and cardiac conduction problems.…”
mentioning
confidence: 99%
“…7 Also, Transcription Factor A Mitochondrial (TFAM) is a key regulator of the transcription of mt-DNA. 7 Santos, et al have shown that ubiquitination of TFAM in diabetes prevents its transport to the mitochondria, which disrupts mitochondrial homeostasis indicating the strong relation with diabetes and mitochondrial dysfunction. 7 Kearns-Sayre Syndrome (KSS) is a rare cause of diabetes in children.…”
mentioning
confidence: 99%
“…The HSP60-70 complex is Londependent, and, importantly, TFAM binds to the HSP70 component. The interaction of TFAM bound to HSP-70 at the nucleus allows for transportation of TFAM into the mitochondria (Santos, Mishra, and Kowluru 2014). Lon can be personified as TFAM's personal trainer, keeping TFAM fit for mitochondrial biogenesis.…”
Section: Tfam Transportmentioning
confidence: 99%
“…This regulates Ca 2+ , leading to decreased protease activity and apoptotic signaling. Santos describes TFAM's binding to HSP60, but at a lower affinity when compared to HSP70 (Santos, Mishra, and Kowluru 2014). TFAM transport may be inhibited in high ROS conditions such as cardiomyopathies.…”
Section: Tfam Transportmentioning
confidence: 99%
See 1 more Smart Citation